A nonflammable phosphate-based localized high-concentration electrolyte for safe and high-voltage lithium metal batteries. Issue 5 (9th February 2022) - Wang, Xiaofei; He, Wenjun; Xue, Haoliang; Zhang, Daoming; Wang, Jin; Wang, Lina; Li, Jun
Abstract : The well-designed electrolyte enables high-voltage Li‖Ni6 Mn2 Co2 O2 batteries with both enhanced safety and superior reversibility. Abstract : Lithium (Li) metal batteries (LMBs) have been considered as promising candidates for next-generation energy storage devices due to the tremendous advantages of Li-metal anodes. However, poor cycling stability and severe safety issues impede the practical application of LMBs. Herein, a nonflammable phosphate-based localized high-concentration electrolyte composed of lithium difluoro(oxalato)borate/dimethyl methyl phosphonate/1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropylether (LiDFOB–DMMP/HFE) is proposed to improve the safety and reversibility of high-voltage LMBs simultaneously. Replacing highly flammable conventional solvents in the electrolyte with flame-retardant DMMP greatly reduces the fire risks of the electrolyte. The dominant reduction of DFOB − anions induces a robust and LiF-rich solid-electrolyte interphase on the Li-metal anode, stabilizing the Li metal/electrolyte interface and leading to dendrite-free Li deposition. An effective cathode electrolyte interphase is generated as well to inhibit structural degradation and transition-metal dissolution of the high-voltage LiNi6 Mn2 Co2 O2 (NMC622) cathode. Moreover, the electrolyte displays a high oxidative stability potential of >5.0 V. Thus, the Li‖NMC622 battery using LiDFOB–DMMP/HFE electrolyte exhibits a superior cyclability with no capacity loss and a high average coulombic efficiency of 99.6% over 100 cycles under a high cutoff voltage of 4.5 V. This emerging electrolyte offers great potential to realize the stable cycling of high-voltage LMBs with fine safety for future applications.